Migration: change of cycle in the relationship between the UE and the Latin America and the Caribbean - Stuhldreher, Amalia (Estudios Internacionales, 2015)
The article addresses the evolution of the immigration issue within the process of bi-regional summits between the EU and Latin America and the Caribbean since 1999. Considering changes in the architecture of Latin American integration and the evolution of the European process, the bi-regional relationship undergoes a change of cycle. Taking account of this evolution, the article discusses on one hand the theoretical framework of the interregionalism, which has framed the analysis and design of policies over the past decades. On the other hand, it focuses on the progress of the dialogue about migration, discussing its real importance within the bi-regional architecture in terms of a potential dynamization of the relationship, considering the global framework.